2021
DOI: 10.1007/s11250-021-02620-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with Ctenocephalides felis flea infestation of peri-urban goats: a neglected parasite in an under-appreciated host

Abstract: Goats are critical in mixed smallholder agricultural systems in lower and middle-income countries, while fleas are important human and animal health concerns around the world. Convenience sampling was used to describe and consider risk factors for flea infestations of peri-urban goats, with the aim of informing the iterative development of animal husbandry and management based control strategies. Seven hundred and ninety-two goats were examined in 228 households across 10 peri-urban communities surrounding Bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Infestations in small ruminants relating to this species have been previously reported in Ethiopia [76], Nigeria [77], Africa [78], and Turkey [79]. The typical hosts of Ctenocephalides sp.…”
Section: Discussionmentioning
confidence: 81%
“…Infestations in small ruminants relating to this species have been previously reported in Ethiopia [76], Nigeria [77], Africa [78], and Turkey [79]. The typical hosts of Ctenocephalides sp.…”
Section: Discussionmentioning
confidence: 81%
“…Certain floor types (i.e., concrete and board) were negatively associated with flea abundance, providing a protective effect. Previous studies reported that thorough and frequent floor cleaning could remove fleas of all developmental stages, as well as organic particles on which larvae feed, and thus could reduce flea infestations [ 4 , 41 ]. Most households reported daily floor sweeping ( Table 1 ), although the dirt floor under the mat covering would be left undisturbed.…”
Section: Discussionmentioning
confidence: 99%
“…Further, presence of livestock was among factors that showed higher risk of flea bites. This is because the presence of livestock enhances flea development and survival because they provide a source of blood for adult fleas to feed, shelter and nesting sites and serve as vehicle for fleas spreading to the new hosts and environments when moving between different areas or come into contact with other hosts [ 56 , 57 ]. Importantly, our previous study found that rodent abundance was higher in agricultural and forest habitats within the study area [ 51 ].…”
Section: Discussionmentioning
confidence: 99%